2019
DOI: 10.1155/2019/8246815
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Electromagnetic Shock Wave Therapy in the Treatment of Cellulite

Abstract: In the past centuries, the human body was undervalued; nowadays, however, it is overvalued, and thus the manifestation of the dissatisfactions regarding the body has been increasing. Most of the time, these dissatisfactions are related to cellulite, which is most common in women. Its treatment is one of the challenges which encourage the development of new therapeutic modalities, among them the shockwave therapy. Objective. To evaluate the efficacy of ESWT in the treatment of cellulite in gluteus and posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…This method molds the shapes and volumes, making them more regular but not modifying the skin surface. Numerous therapeutic modalities have been proposed for the treatment of cellulite; among these are cosmetics, therapeutic massage, radiofrequency, ultrasound, laser therapy, carboxytherapy, intense pulsed light, subcision vibration/oscillation platform therapy, and most recently, extracorporeal shockwave therapy (ESWT) or acoustic wave therapy (AWT) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This method molds the shapes and volumes, making them more regular but not modifying the skin surface. Numerous therapeutic modalities have been proposed for the treatment of cellulite; among these are cosmetics, therapeutic massage, radiofrequency, ultrasound, laser therapy, carboxytherapy, intense pulsed light, subcision vibration/oscillation platform therapy, and most recently, extracorporeal shockwave therapy (ESWT) or acoustic wave therapy (AWT) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…47 Between the initial evaluation and the 3-month follow-up after completion of treatment, the Celluqol scores significantly improved ( p < .05). 47…”
Section: Psychological Aspectsmentioning
confidence: 91%
“…46 The Celluqol scale was also used to evaluate patient satisfaction in 27 women undergoing ESWT. 47 Between the initial evaluation and the 3month follow-up after completion of treatment, the Celluqol scores significantly improved (p , .05). 47 The BODY-Q cellulite scale is a 15-item assessment that measures how bothered the patient is by the appearance of cellulite.…”
Section: Treatment Satisfactionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study in women that received 10 sessions of acoustic wave therapy, evaluated the biophysical changes induced by this treatment modality by measuring skin viscoelasticity with the Cutometer®, and thickness of hypodermis with diagnostic ultrasound. At the 3‐month follow‐up results showed that the treatment led to significantly improved skin elasticity and decreased skin deformation 24 …”
Section: Energy‐based Devices For Cellulitementioning
confidence: 99%